The Mehri language of Oman - Rubin, Aaron D., 1976- (Studies in Semitic languages and linguistics, 2010)
This volume contains a detailed grammatical description of Mehri, an unwritten Semitic language spoken in Oman and Yemen. It is the first grammar of its kind, and the first of any Modern South Arabian language in a century.